2017
DOI: 10.1071/rd15200
|View full text |Cite
|
Sign up to set email alerts
|

Localisation of RNAs and proteins in nucleolar precursor bodies of early mouse embryos

Abstract: Early embryos of all mammalian species contain morphologically distinct but transcriptionally silent nucleoli called the nucleolar precursor bodies (NPBs), which, unlike normal nucleoli, have been poorly studied at the biochemical level. To bridge this gap, here we examined the occurrence of RNA and proteins in early mouse embryos with two fluorochromes - an RNA-binding dye pyronin Y (PY) and the protein-binding dye fluorescein-5'-isothiocyanate (FITC). The staining patterns of zygotic NPBs were then compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 53 publications
1
11
0
Order By: Relevance
“…Upon fertilization, the NLBs that disappeared during oocyte meiotic maturation reappear in both maternal and paternal pronuclei of zygotes in the form of nucleolus precursor bodies (NPBs), which persist throughout the first four cell cycles [52] (Figure 2 for RNA and detectable amounts of RNA appear on the NPB surface only after resumption of rRNA gene transcription [53]. Accordingly, during the late two-cell and four-cell stages, UBF and Nopp140, two nucleolar proteins that are associated with FC and DFC of the nucleolus, localize around the periphery of the NPBs [51].…”
Section: Box 1 Preimplantation Developmental Stagesmentioning
confidence: 99%
“…Upon fertilization, the NLBs that disappeared during oocyte meiotic maturation reappear in both maternal and paternal pronuclei of zygotes in the form of nucleolus precursor bodies (NPBs), which persist throughout the first four cell cycles [52] (Figure 2 for RNA and detectable amounts of RNA appear on the NPB surface only after resumption of rRNA gene transcription [53]. Accordingly, during the late two-cell and four-cell stages, UBF and Nopp140, two nucleolar proteins that are associated with FC and DFC of the nucleolus, localize around the periphery of the NPBs [51].…”
Section: Box 1 Preimplantation Developmental Stagesmentioning
confidence: 99%
“…Firstly, at the 1-cell stage, several teams have suggested that NPBs ensure the correct remodeling of heterochromatin regions composed of “major satellite” sequences (Ogushi and Saitou 2010 ; Jachowicz et al 2013 ; Fulka and Langerova 2014 ; Kyogoku et al 2014 ). Secondly, these NPBs serve as a platform for the development of functional nucleoli from the end of the 2-cell stage through the morula stage (Zatsepina et al 2003 ; Lavrentyeva et al 2015 ; Koné et al 2016 ). In the mouse, the removal of nucleolus-like structures from the growing oocyte, or the removal of NPBs at the start of the 1-cell stage, can lead to an arrest of development at the 2-cell stage.…”
Section: Introductionmentioning
confidence: 99%
“…transformation of dense nucleolar precursor bodies (NPBs) into functional reticulated nucleoli. Active nucleoli consist of fibrillar centres (FCs), a dense fibrillar component (DFC) and a granular component (GC) (Lavrentyeva et al , 2015).…”
Section: Introductionmentioning
confidence: 99%